2010
DOI: 10.1891/1078-4535.16.2.68
|View full text |Cite
|
Sign up to set email alerts
|

Leading and Managing an Intergenerational Workforce

Abstract: Focus group discussions with four generations of staff nurses identified five themes that participants believed must be addressed in order to make the current work environment a desirable place to conduct their careers as nurses. These themes are: transitioning from student to nurse, managing difficult staffing conditions, maintaining morale, dealing with safety matters, and building relationships that enhance teamwork. Manager challenges are discussed in relation to each theme and suggested leadership strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(75 citation statements)
references
References 6 publications
6
69
0
Order By: Relevance
“…Living through particular historical or environmental events contributes to a generation sharing the same beliefs and attitudes (Strauss and Howe, 1991). These common beliefs and values have implications for multigenerational work environments, with research illustrating significant differences in the career aspirations and expectations between different generation cohorts (Zemke et al, 2000;Hu et al, 2004;Dols et al, 2010). Wilson et al (2008) have shown intergenerational disparity in nursing staff retention, with markers of job satisfaction, including pay and benefits, rated higher by Baby Boomers than Generation X or the Millennials.…”
Section: An Inter-generational Workforcementioning
confidence: 99%
“…Living through particular historical or environmental events contributes to a generation sharing the same beliefs and attitudes (Strauss and Howe, 1991). These common beliefs and values have implications for multigenerational work environments, with research illustrating significant differences in the career aspirations and expectations between different generation cohorts (Zemke et al, 2000;Hu et al, 2004;Dols et al, 2010). Wilson et al (2008) have shown intergenerational disparity in nursing staff retention, with markers of job satisfaction, including pay and benefits, rated higher by Baby Boomers than Generation X or the Millennials.…”
Section: An Inter-generational Workforcementioning
confidence: 99%
“…This condition helps the groups to face situations which change constantly, assisting in the recognition of those in whom one can trust and on whom one can rely in order to overcome difficulties (10)(11) .…”
Section: Motivation For Taking On the Management Positionmentioning
confidence: 99%
“…KH theorized that a nurse without obvious leadership traits in a role where she provided assistance to the general practitioner, who had not undertaken any postgraduate study and who was of the older 'baby boomer generation 16 ' may not have the same attitude to GNs as EPN2. KH theorized that this positive attitude towards best practice and information use was a property of 'embracing graduate nurses'.…”
Section: Kh 'And How Do You Find Them (Gn's) In Terms Of Their Informmentioning
confidence: 99%